An Empirical Study of Consciousness and Usage of Consumer Rights empowered by Consumer Protection Act - Diksha Goel, Ravi Kumar Gupta, A.K. Vashisht, Ishwar Mittal (Journal of Informatics Education and Research, 2024)
Indian consumers come across a variety of issues in their day-to-day interactions with merchants and other organizations. Consumer protection is dependent on their awareness of these issues. Consumer must be aware about such unfair practices of scrupulous traders in order to play safe at an hour of purchase. To safeguard consumer interests in the past, the government, corporate organizations, consumer clubs, and consumers themselves took a variety of legal, regulatory, and non-legislative actions. But in this era of digitalization, customer expectations for easier accessibility, greater options, simple payment methods, better services, and convenient shopping increase, poses more challenges on the issue related to consumer protection and consciousness. The Government responded by enacting the historic Consumer Protection Act, 2019 and replaced the Consumer Protection Act, 1986 intending to enable quick and effective administration and settlement of consumer complaints, in order to solve the new set of difficulties faced by consumers in this digital era. In order to determine, assess, and interpret the extent to which people are using provisions of Consumer grievance redressal machinery available under CPA 2019, the present work used survey research. Two groups of respondents were segregated. Some consumers found fault in product purchased / deficiency in services but not conscious about making complaint. Another group of consumers who took a further course of action to resolve their complaint. Consumers were also enquired about the extent to which they exercise their rights.